Project ECHO, Communities of Practice, and a Successful Opioid Reduction Outcome - Ryan Spaulding; Whitney Henley; Shawna Wright; Peggy Parker (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Introduction: Project ECHO offers a virtual, interactive sessions to connect health care providers with specialists. Evaluation efforts have focused on quantitatively identifying the implementation process and provider's perspectives. This case demonstrates that patient success stories are able to provide a wealth of information that can be used as part of evaluation efforts.  Background: Through presenting a patient case to the expert panel of a Pain Prescribing ECHO, an Advanced Practice Registered Nurse was able to assist a desperate patient who suffered from negative effects of opioid use for many years. This paper explores the experiences of the care provider during the ECHO sessions as well as afterwards when recommendations from the ECHO team were used by the provider.  Patient success story: The provider used the guidance from the ECHO to develop several new strategies to reduce the patient's opioid use. After pursuing multiple options, the patient has enjoyed a vast improvement in quality of life and a decrease in the amount of pain experienced.  Discussion: Using patient stories as qualitative outcome measures may assist ECHO programs in gaining insight into program effectiveness and demonstrate the value of the ECHO model.